LP-Sasakian Manifolds Equipped with Zamkovoy Connection and Conharmonic Curvature Tensor - Abhijit Mandal; Ashoke Das (Journal of the Indonesian Mathematical Society, 2021)
In this paper we have proved some results on conharmonically flat, quasi conharmonically flat and φ-conharmonically flat LP-Sasakian manifolds with respect to Zamkovoy connection. Also, we study generalized conharmonic φ-recurrent LP-Sasakian manifolds with respect to Zamkovoy connection. Moreover, we study LP-Sasakian manifolds satisfying K*(ξ,U)∘R*=0, where K* denotes conharmonic curvature tensor and R* denotes Riemannian curvature tensor with respect to Zamkovoy connection.